2020
DOI: 10.1021/acs.macromol.9b02739
|View full text |Cite
|
Sign up to set email alerts
|

Nanostructure Control of a Regioregular Poly(3-alkylthiophene) Using an Oligopeptide Side Chain

Abstract: With the aim of probing the competitive roles of π–π stacking and hydrogen bonding in modulating the aggregation state of conjugated polymers, a functionalized thiophene monomer containing a clickable azide group was copolymerized with 2,5-dibromo-3-hexylthiophene via Grignard metathesis (GRIM) to form either a block or a random copolymer, which was then covalently linked via click chemistry to a tetrapeptide (Gly-Val-Gly-Val) that is prone to forming β-sheets. A series of polythiophene–peptide hybrids with si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 44 publications
0
4
0
Order By: Relevance
“…The oligothiophene conjugated peptide was first developed by Bäuerle and coworkers in 2004, and since then, different oligothiophene-peptide and polythiophene-peptide conjugated systems have been developed to improve solubility and physicochemical properties. , Wan and coworkers have developed a series of polythiophene conjugated peptide hybrid systems exhibiting tunable self-assembly behavior . Lin et al .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The oligothiophene conjugated peptide was first developed by Bäuerle and coworkers in 2004, and since then, different oligothiophene-peptide and polythiophene-peptide conjugated systems have been developed to improve solubility and physicochemical properties. , Wan and coworkers have developed a series of polythiophene conjugated peptide hybrid systems exhibiting tunable self-assembly behavior . Lin et al .…”
Section: Introductionmentioning
confidence: 99%
“…40,44 Wan and coworkers have developed a series of polythiophene conjugated peptide hybrid systems exhibiting tunable self-assembly behavior. 45 Lin et al 46 have reported an electrochemical biosensor consisting of a Gly-Gly-His tripeptide covalently attached to poly(3-thiopheneacetic acid) (PTAA). Here, the authors have shown that the Gly-Gly-His-modified PTAA electrode exhibited a greater affinity toward Cu 2+ ions compared to the other ions and the electrode was found to be highly selective for Cu 2+ ions in the range of 0.02−20 μM.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Thereafter, many oligo/poly thiophene peptide conjugates have been developed ,, to improve the physicochemical properties. Wan and co-workers covalently linked a series of PT-tetrapeptide (Gly-Val-Gly-Val) conjugates via click chemistry and observed that the self-assembly strongly depends on the quantity of the tetrapeptide side chain; however, the effect of PT-regioregularity was found to be less important. Both block and random copolymers of PT self-assemble into nanofibers with low oligopeptide contents (<33 mol %), while high oligopeptide contents (>40 mol %) form spheres of 0.05–1.0 μm diameter.…”
Section: Polythiophene-peptide Conjugatesmentioning
confidence: 99%
“…This attention could be conceived to have originated from the early compositional introductions of Chmielewski, Bäuerle, and Nowick, who joined peptide sequences with π-electron cores. This attention is currently manifest in the many modern day examples showcasing the structures, morphologies, and properties of these hybrid bioelectronic materials. In general, π-peptide conjugates can self-assemble into hierarchical nanostructures such as tapes and fibrils in line with many standard oligopeptides that are capable of forming amyloid-like nanomaterials. Importantly, they offer the additional ability to foster intermolecular π-stacking of the electronic cores which is required for energy migration in a broad sense.…”
Section: Introductionmentioning
confidence: 99%